PENYELESAIAN SENGKETA PENDAFTARAN TANAH: (Studi Kasus Putusan Mahkamah Agung No: 15/PDT.G/2014/PN.RGT.TLK) - Amanda Namira Yunir (2021)
As a rule of law country, Indonesia has principles to guarantee certainty, order, and protection of laws based on truth and justice. To realize these principles, government regulations were issued by law. In the land sector, the government issued several regulations, such as Law no. 5 of 1960 concerning Basic Agrarian Principles and Government Regulation No. 24 of 1997 concerning Land Registration. In the dispute which will be discussed in this journal, there is a legal issue in the form of a conflict of norms, in which the Plaintiff has not received legal certainty for his land because the land certificate is still in the name of the Defendant. With the sale and purchase of land, there should have been a transfer of land rights from Defendant to the Plaintiff. The transfer of land rights must be registered by the Conveyancer. This research aims to increase public awareness, especially land sellers, to do their obligations in order to create profitable buying and selling activities that gives benefit for both parties. This research is a juridical-normative legal research, using case approach and statute approach. The results of this study indicate the inconsistency of dispute resolution according to the Supreme Court Decision No: 15 / Pdt.G / 2014 / PN.Rgt.Tlk with the applicable laws and regulations, which will be discussed in this journal.